The Implications of Utilizing Artificial Intelligence-Based Parenting Technology on Children's Mental Health: A Literature Review - Yunike, Yunike; Rehana, Rehana; Misinem, Misinem; Kusumawaty, Ira (Poltekkes Kemenkes Palu, 2023)
The study aims to look at the development of artificial intelligence to support positive parenting and help improve children's mental health. This research method uses the PRISMA approach through a search process using the keywords